NEW SILK ROADS : THE PRESENT AND FUTURE OF THE WORLD - PETER FRANKOPAN (LONDON BLOOMSBURY, 2018)
The New Silk Roads takes a fresh look at the relationships being formed along the length and breadth of the ancient trade routes today. The world is changing dramatically and in an age of Brexit and Trump, the themes of isolation and fragmentation permeating the western world stand in sharp contrast to events along the Silk Roads, where ties are being strengthened and mutual cooperation established. This prescient contemporary history provides a timely reminder that we live in a world that is profoundly interconnected. Following the Silk Roads eastwards from Europe through to China, by way of Russia and the Middle East, Peter Frankopan assesses the global reverberations of continual shifts in the centre of power - all too often absent from headlines in the west.
Keywords: International economic relations; Asia - Silk Road; East and West